Hubungan Tingkat Pengetahuan dengan Kepatuhan Minum Obat ARV di Ruang Khusus CST Puskesmas Kemayoran Jakarta - Donny Prastyo; Rahayu Winarti; Menik Kustriyani (Universitas Malahayati Lampung, 2026)
ABSTRACT HIV/AIDS continues to be one of the leading global health challenges. Antiretroviral therapy (ART) has proven effective in reducing viral load, yet its success largely depends on patient adherence. Knowledge is often considered an important factor influencing adherence, although previous research has shown inconsistent results.